Emotion and cognition in high and low stress sensitive mouse strains: a combined neuroendocrine and behavioral study in BALB/c and C57BL/6J mice - Brinks, Vera; Van Der Mark, Maaike; De Kloet, Ronald; Oitzl, Melly S. (Frontiers in Behavioral Neuroscience, 2007)
Emotionally arousing experiences and stress influence cognitive processes and vice versa. Understanding the relations and interactions between these three systems forms the core of this study. We tested two inbred mouse strains (BALB/c, C57BL/6J; male; 3-month-old) for glucocorticoid stress system markers (expression of MR and GR mRNA and protein in hippocampus, amygdala, and prefrontal cortex; blood plasma corticosterone), used behavioral tasks for emotions and cognitive performance (elevated plus maze, holeboard) to assess the interdependence of these factors. We hypothesize that BALB/c mice have a stress-vulnerable neuroendocrine phenotype and that emotional expressions in BALB/c and C57BL/6J mice will differentially contribute to learning and memory. We applied factor analyses on emotional and cognitive parameters to determine the behavioral structure of BALB/c and C57BL/6J mice. Glucocorticoid stress system markers indeed show that BALB/c mice are more stress-vulnerable than C57BL/6J mice. Moreover, emotional and explorative factors differed between naïve BALB/c and C57BL/6J mice. BALB/c mice display high movement in anxiogenic zones and high risk assessment, while C57BL/6J mice show little movement in anxiogenic zones and display high vertical exploration. Furthermore, BALB/c mice are superior learners, showing learning related behavior which is highly structured and emotionally biased when exposed to a novel or changing situation. In contrast, C57BL/6J mice display a rather ‘‘chaotic’’ behavioral structure during learning in absence of an emotional factor. These results show that stress vulnerability coincides with more emotionality, which drives well orchestrated goal directed behavior to the benefit of cognition. Both phenotypes have their advantage depending on environmental demands.